Oxford international lower secondary English student book 6 - Barber, Alison; Redford, Rachel (Karachi Oxford university press, 2023)
This edition of Oxford International Lower Secondary English gives students the skills they need to become confident communicators with a strong grasp of English language, vocabulary and grammar. Students discover the joy of learning through speaking and listening, reading extracts from around the world, writing and performing.
Keywords: English - Textbook; Oxford - English Text book